Retrograde Balloon-Assisted Deep Enteroscopy in the Diagnosis of Metastatic Melanoma. (30th June 2021) - Barge, William; Albertini, Mark R.; Cold, Christopher; Abbott, Daniel; Gopal, Deepak
Abstract : A 74-year-old male with a history of metastatic melanoma presents with persistently abnormal small bowel findings on PET-CT scan. The patient had persistent FDG uptake near the ileocolic junction on imaging, concerning for metastatic melanoma. Capsule endoscopy demonstrated ulcerated mucosa in the distal ileum. This area was biopsied and tattooed via retrograde double-balloon enteroscopy to confirm the diagnosis of metastatic melanoma and facilitate subsequent small bowel resection. The case illustrates a unique case of metastatic melanoma to the small bowel and the utility of capsule endoscopy and balloon-assisted enteroscopy to assist in diagnosis and management of metastatic disease.